2022
DOI: 10.1093/plcell/koac325
|View full text |Cite
|
Sign up to set email alerts
|

Proton exchange by the vacuolar nitrate transporter CLCa is required for plant growth and nitrogen use efficiency

Abstract: Nitrate is a major nutrient and osmoticum for plants. To deal with fluctuating nitrate availability in soils, plants store this nutrient in their vacuoles. CLCa, a 2NO3-/1H+ exchanger localized to the vacuole in Arabidopsis (Arabidopsis thaliana), ensures this storage process. CLCa belongs to the CLC family, which includes anion/proton exchangers and anion channels. A mutation in a glutamate residue conserved across CLC exchangers is likely responsible for the conversion of exchangers to channels. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…In this scenario, a transitory elevated cytosolic nitrate level would decrease nitrate uptake, increase the nitrate efflux from the cells and/or the assimilation pathways through the nitrate reductase (NR). This was confirmed in a recent study demonstrating that the inhibition of nitrate storage in the vacuole leads to an increase of the NR activity and a better NUE (Hodin et al, 2023).…”
Section: Nitrate Fluxes Through Clca and Nrt27 Alter Root Nitrate Uptakesupporting
confidence: 75%
“…In this scenario, a transitory elevated cytosolic nitrate level would decrease nitrate uptake, increase the nitrate efflux from the cells and/or the assimilation pathways through the nitrate reductase (NR). This was confirmed in a recent study demonstrating that the inhibition of nitrate storage in the vacuole leads to an increase of the NR activity and a better NUE (Hodin et al, 2023).…”
Section: Nitrate Fluxes Through Clca and Nrt27 Alter Root Nitrate Uptakesupporting
confidence: 75%
“…CLCa and CLCb are important transporters responsible for vacuolar NO 3 – influx and efflux. , Under low N, reduced CLCa expression and increased CLCb expression contributed to efficient long-distance NO 3 – translocation from roots to shoots, which was undertaken by the elevated expression of NPF7.3 / NRT1.5. Therefore, we investigated the expression of TaCLCa and TaCLCb in the roots of ZM578 and XM26; we found that the low-N-tolerant cultivar ZM578 presented lower expression of TaCLCa-6A and higher expression of TaCLCb-6D than the low-N-sensitive cultivar XM26, particularly under N limitation (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the molecular mechanisms underlying efficient N use in the three major cereal crop species, namely, rice, maize, and wheat, although great progress has been made in rice 40,41 and maize, 42,43 few noticeable achievements have been obtained in wheat. 35 Plants tend to retain N in source organs when N nutrients are sufficient; when the N status is relatively low, plants remobilize N more efficiently. 44 Therefore, NUE is usually significantly higher under low N conditions than under high N conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Proteins of the CLC (ChLoride Channel) family are found in representatives of all kingdoms [ 17 , 18 , 19 , 20 , 21 ] and play important roles in the transport of Cl − and NO 3 − in plants [ 20 , 22 ]. Contrary to animal CLCs, all of the plant CLCs whose subcellular localization has been studied have been found so far in intracellular membranes, including the tonoplast [ 20 , 22 , 23 ]. The plant CLC family includes Cl − /H + - and NO 3 − /H + -antiporters along with chloride channels [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with Cl − transport into the organelles, the Cl − /H + antiport stimulates acidification of the organellar lumen through V-ATPase activation mediated by neutralization of positive charges entering the lumen when the ATPase operates [ 26 ]. NO 3 − /H + -antiporter AtCLCa was shown to be involved in NO 3 − storage in vacuoles and regulation of NO 3 − concentrations in the cytosol of Arabidopsis thaliana cells [ 22 , 27 , 28 ]. It was shown that, in glycophytes, salt-sensitive plants, the CLC proteins participated in vesicular trafficking, response to medium salinization, and nitrogen nutrition.…”
Section: Introductionmentioning
confidence: 99%